Anatomical Description of the Presence and Variability of the Digital Manica Flexoria in the Equine Digital Flexor Tendon Sheath. (6th May 2016) - Jordana, M.; Cornillie, P.; Oosterlinck, M.; Simoens, P.; Pille, F.; Martens, A.
Summary: During endoscopy (tenoscopy) of the distal aspect of the equine digital flexor tendon sheath (DFTS), the digital manica flexoria can be visualized connecting the distal branches of the superficial digital flexor tendon. However, this structure has been inconsistently described and variably named in the veterinary literature. The objectives of this study were to describe the presence, configuration and variability of the digital manica flexoria in the equine distal limb. Dissection of 144 equine cadaveric limbs revealed the presence of this structure in all the feet, although different types and conformations were identified. In the forelimbs, a membranous digital manica flexoria predominated (94%; P  <   0.001), in particular a synovial bridge type (83%; P  <   0.001). In the hindlimbs, a tendinous digital manica flexoria predominated (93%; P  <   0.001), in particular the oblique‐crossing of tendinous bundles (61%; P  <   0.001). Passage dorsal to the digital manica flexoria towards the distal DFTS was only possible in 22 of the 144 limbs, all forelimbs. Clinicians should be aware of the intra‐ and inter‐individual anatomical variations of the digital manica flexoria to avoid misinterpretation during ultrasonographic and tenoscopic examinations of the DFTS.